Os novos paradigmas da educação social: atuação do educador social em Vila Velha-ES - limites e possibilidades na Grande Terra Vermelha - Marques, Marcelino (2014)
This research points to the news paradigms of social education that has been built in the national and international spheres by means of social pedagogy. The justification if the agenda by the growing integration of Social Educator in schools. I identify the profile and the performance of social educators through the full-time education. I chose the big red earth, in municipality of Vila Velha-ES for being a region with growing presence of Social Educators. I show the debates around regulation of the activity of Social Education, enabling the practice of the profession. The methodology is focused on speeches of the subjects of research and do not follow the traditional methodologies that present the results at the end of research. I decided to present the theoretical references along with the speeches of the subjects of the research, which enabled a greater understanding of reality. The references are frameworks of social education, social pedagogy and popular education, all with a sociological gaze. Expose some thoughts that have been made about the social and start launching the discourses of social educators popular in freiriana perspective and full-time education in Brazil. Expose about changes in the organization of work and education and show that the performance of Social Educators happens at a time of globalization and new labor reconfigurations from educational reforms of the years 1990. Throw the dialogue of Social Educators to emphasize that even with the changes many practices stay the same and the precariousness of working conditions persists. Show the concerns, difficulties in spaces that undermine the work of Social Educators and also present in their speeches that they suffer discrimination within the school by other education professionals. Finally, the testimony of educators confirms the precarious working conditions. Present some (in) conclusions about the importance of Social Educators in schools as a new performance space through social education and show that regulation of social education activity can improve education in Brazil